Learning system management based on teaching factory in Indonesia - ABDUL HARIS (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: The study’s overarching purpose is to describe 1) The Teaching Factory-inspired classroom environment at SMK Muhammadiyah 1 Klaten and 2) The SMK Muhammadiyah 1 Klaten faculty’s use of Teaching Factory inspired professional development activities. Three) SMK Muhammadiyah 1 Klaten student’ Teaching Factory-inspired learning characteristics.Methodology: The methodology of this study is qualitative, and it takes an ethnographic approach. The students of SMK Muhammadiyah 1 Klaten conducted this study. This study focuses on SMK Muhammadiyah 1 Klaten’s school administrator. Interviews, observations, and written documentation were used to compile the files. We use interstates analysis, arranged file analysis, and unarranged file analysis to examine files. A file validation test employs credibility, transferability, confirmability, and dependability.Findings: The study found that 1) SMK Muhammadiyah 1 Klaten’s management of education is improving service to stakeholders through the implementation of a learning strategy based on the principles of Teaching Factory, and 2) The educators at SMK Muhammadiyah 1 Klaten have completed a training program based on Teaching Factory, 3) Through the educational process, students acquire the knowledge, character traits, and abilities they need to enter the workforce or launch a successful business upon graduation.Novelty/Implications: This research uncovered new information about the management of educational systems, especially the management of the teaching factory, which is significantly more effective and efficient, especially at the Vocational High School level.